Monoamine responses to acute and chronic aerobic exercise in normotensive and hypertensive subjects - Arida, Ricardo Mario (1998)
OBJECTIVES: The purpose of the present study was to compare the plasma and serum monoamine levels in sedentary, untrained normotensive and hypertensive men at rest with levels measured after an acute bout of exercise and to compare similar measurements following a 12-week aerobic training program. PLACE OF STUDY: The data obtained for this study was collected from a clinic for the prevention of heart disease and cardiac rehabilitation (FITCOR) and analyzed in the Federal University of São Paulo (EPM), Laboratory of Experimental Neurology. SUBJECTS: Two groups of untrained male subjects, i.e., normotensive (N=16) and hypertensive (N=19), were submitted to an acute bout of exercise to analyze the acute effect of exercise on the monoamine levels.To study the chronic effect of exercise (physical training program), some individuals of each group were arranged in two other groups; normotensive (N=11) and hypertensive (N=8). MEASUREMENT: Plasma catecholamines and serum serotonin levels were determined by high performance liquid chromatography coupled with electrochemical detection. RESULTS: A significant reduction in diastolic blood pressure at rest was observed in the hypertensive group after the physical training program (p < 0.05). Only the mean plasma noradrenaline concentration increased significantly post-exercise in all groups of individuals (acute effect of exercise - p < 0.01 for untrained normotensive and hypertensive; chronic effect of exercise - p < 0.001 for untrained and trained normotensive, p < 0.01 for untrained and trained hypertensive). CONCLUSION: These data show the beneficial effect of physical exercise in reducing the blood pressure in hypertensive patients, which does not seem to be related to changes in circulating monoamines.